2019
DOI: 10.1097/bsd.0000000000000771
|View full text |Cite
|
Sign up to set email alerts
|

Wrong Site Spine Surgery in the Veterans Administration

Abstract: Study Design: Basic descriptive analysis was performed for the incident characteristics of wrong level spinal surgery in the Veterans Health Administration (VHA). Objective: To determine the frequency of reported occurrence of incorrect spine level surgery in the VHA, causal factors for the events, and propose solutions to the issue. Summary of Background Data: Wrong site surgery is one of the most common ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Notably, 50-67% of spine surgeons have directly experienced WLS over their careers [Table 1]. [12,14,20] Mody et al (2008) observed that 207 (50%) neurosurgeons had experienced WLS (spinal) once or more during their careers; the overall incidence was 1/3110 spinal cases. [14] Watts et al (2019) reported the same 50% incidence of WLS over spine surgeons' careers, a frequency distinctly unchanged by the 11 year interval between the two studies.…”
Section: Incidence Of Wls For Individual Spinal Surgeons Over Their Entire Careersmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, 50-67% of spine surgeons have directly experienced WLS over their careers [Table 1]. [12,14,20] Mody et al (2008) observed that 207 (50%) neurosurgeons had experienced WLS (spinal) once or more during their careers; the overall incidence was 1/3110 spinal cases. [14] Watts et al (2019) reported the same 50% incidence of WLS over spine surgeons' careers, a frequency distinctly unchanged by the 11 year interval between the two studies.…”
Section: Incidence Of Wls For Individual Spinal Surgeons Over Their Entire Careersmentioning
confidence: 99%
“…[14] Watts et al (2019) reported the same 50% incidence of WLS over spine surgeons' careers, a frequency distinctly unchanged by the 11 year interval between the two studies. [20] Interestingly, Mayer et al (2014) reported a higher 67% incidence of WLS involving thoracolumbar procedures over surgeons' careers; this frequency was somewhat higher utilizing X-ray (56%) alone vs. fluoroscopy (44%) to intraoperatively confirm the correct spinal operative levels. [12]…”
Section: Incidence Of Wls For Individual Spinal Surgeons Over Their Entire Careersmentioning
confidence: 99%
See 3 more Smart Citations